2021
DOI: 10.1101/2021.05.27.445979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

de novo variant calling identifies cancer mutation profiles in the 1000 Genomes Project

Abstract: Detection of de novo variants (DNVs) is critical for studies of disease-related variation and mutation rates. We developed a GPU-based workflow to call DNVs, using 602 trios from the 1000 Genomes Project as a control. We detected 445,711 DNVs, having a bimodal distribution, with peaks at 200 and 2000 DNVs. The excess DNVs are cell line artifacts that are increasing with cell passage. Reduction in DNVs at CpG sites and in percent of DNVs with a paternal parent-of-origin with increasing number of DNVs supports t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
(89 reference statements)
2
4
0
Order By: Relevance
“…We observed two prominent modes and a long tail of mutation count across offspring. This is also consistent with previous mutation calling in the 1000 genomes project (1kGP) offspring and is thought to result from LCL culture age 35 ( Fig 1A ). Only 0.73% of mutations were functional as predicted by a SNPeff 36 (4.3t) high or moderate variant impact score.…”
Section: Resultssupporting
confidence: 91%
“…We observed two prominent modes and a long tail of mutation count across offspring. This is also consistent with previous mutation calling in the 1000 genomes project (1kGP) offspring and is thought to result from LCL culture age 35 ( Fig 1A ). Only 0.73% of mutations were functional as predicted by a SNPeff 36 (4.3t) high or moderate variant impact score.…”
Section: Resultssupporting
confidence: 91%
“…The prevalence of mosaic DNRTs in 1KGP (17%) could be explained by somatic DNTRs occurring in cell culture. Indeed, a higher mosaic rate for SNP/Indel has been reported on the same data, attributed to ongoing mutation processes in cell culture (Byrska-Bishop et al 2022; Ng et al 2021). As a comparison, the mosaic DNRTs in GMKF was 12%, likely due to early embryonic events.…”
Section: Resultssupporting
confidence: 54%
“…As large cohort studies usually have blood or saliva samples with standard depth (∼30X) WGS, only very early embryonic mosaic mutations whose prevalence across tissues is high enough are identified. Earlier trio-based studies on SNVs with ∼30-40X WGS have shown that besides the ∼100 germline de novo small mutations (Jónsson et al 2017; Kong et al 2012), a small number of proband mosaic mutations were identified (Byrska-Bishop et al 2022; Ng et al 2021). Similarly for de novo retroelements, we identified variants of both germline and proband mosaic origin.…”
Section: Resultsmentioning
confidence: 99%
“…The expected number of germline DNMs is $100 per child (Jo ´nsson et al, 2017;Kong et al, 2012), which suggests that the mean number of singletons among children exceeds the expectation by about a factor of 10, although this varies rather widely from sample to sample (Figure S1E). Given that all 1kGP samples are derived from LCLs of various ages, these additional singletons likely represent somatic artifacts from cell-line propagation (Ng et al, 2021), as well as some false positive calls. As evidence of the presence of somatic artifacts, we observed aneuploidy of allosomes in 0.94% of the samples and sub-chromosomal level mosaic CNVs on multiple autosomes (Figure S2).…”
Section: Ll Open Accessmentioning
confidence: 99%